Decay of Strong Solutions for 4D Navier-Stokes Equations Posed on Lipschitz Domains - N. A. Larkin (Advances in Mathematical Physics)
Initial-boundary value problems for 4D Navier-Stokes equations posed on bounded and unbounded 4D parallelepipeds were considered. The existence and uniqueness of regular global solutions on bounded parallelepipeds and their exponential decay as well as the existence, uniqueness, and exponential decay of strong solutions on an unbounded parallelepiped have been established provided that initial data and domains satisfy some special conditions.